Quantitative real-time analysis of the efflux by the MacAB-TolC tripartite efflux pump clarifies the role of ATP hydrolysis within mechanotransmission mechanism - Hager Souabni (Nature Portfolio, 2021)
Souabni et al. introduce a new analytical method for the study of ABC tripartite efflux pumps, by using a lipid scaffold that mimics the protein’s native environment and a spectroscopic assay, employing quantum dots (QD), that monitors ATP hydrolysis and substrate transport in real-time. When applied to MacAB-TolC tripartite pump complex, results suggest high coupling efficiency between transport and energy consumption in the system.